Litterfall Production and Decomposition in a Mined Area Revetetated with Cassia siamea - Liris Lis Komara; Veronika Murtinah; Dian Anggraini; Risma (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: Soil nutrients in ex-coal mining land are very low, therefore it needs to be restored by restoring the nutrient cycle through litter productivity and decomposition. Aim: This study was conducted to determine the litter production and decomposition rates of Cassia siamea and nutrient return on the reclaimed land of PT. Kaltim Prima Coal. Methods: Litter production data were collected using litter traps for 6 months and for decomposition rates using litter bags for 3 months. The contents of C, N, C/N, P, K, cellulose hemicellulose and lignin were taken from the litter. Results: The results showed that there was a positive correlation between waste production and temperature and wind speed and a negative correlation between waste production and rainfall and humidity. Nitrogen and phosphorus content were positively correlated with reclamation age. Litterfall contributes nutrients to the soil in the following order C>N>K>P. Cassia siamea litter has an average decomposition rate of  0.073611 kg m-2 yr-1 or 0.736114 tons ha-1 yr-1.   The very large decomposition rate in the first two weeks was because at the beginning of decomposition the decomposed part of the litterfall contained high levels of water and nitrogen which could increase the decomposition rate. Conclusion: The rate of litterfall production increases with the age of reclamation. There is a positive correlation between litterfall production and temperature and wind speed. There is a negative correlation between litterfall production and rainfall and humidity.